Disrupted Brain Structural Connectivity Network in Subcortical Ischemic Vascular Cognitive Impairment With No Dementia - Sang, Linqiong; Liu, Chen; Wang, Li; Zhang, Jingna; Zhang, Ye; Li, Pengyue; Qiao, Liang; Li, Chuanming; Qiu, Mingguo (Frontiers in Aging Neuroscience, 2020)
The alteration of the functional topological organization in subcortical ischemic vascular cognitive impairment with no dementia (SIVCIND) patients has been elucidated by previous neuroimaging studies. However, little is known regarding the changes in the structural connectivity of brain networks in SIVCIND patients. In this study, a total of 27 subjects, consisting of 13 SIVCIND patients and 14 normal controls, were recruited. Each of the structural connectivity networks was constructed by diffusion tensor tractography. Subsequently, graph theory and network-based statistics (NBS) were employed to analyze the whole-brain mean factional anisotropy matrix. After adjustments for age, gender, and duration of formal education, the clustering coefficients and global efficiency were significantly decreased and the mean path length was significantly increased in SIVCIND patients compared with normal controls. Using a combination of four network topological parameters as the classification feature, a classification accuracy of 78% was obtained by leave-one-out cross-validation for all subjects with a sensitivity of 69% and a specificity of 86%. Moreover, we also found decreased structural connections in the SIVCIND patients, which mainly concerned fronto-occipital, fronto-subcortical and tempo-occipital connections (NBS corrected, p<0.01). Additionally, significantly altered nodal centralities were found in several brain regions of the SIVCIND patients, mainly located in the prefrontal, subcortical, and temporal cortices. These results suggest that cognitive impairment in SIVCIND patients is associated with disrupted topological organization and provide structural evidence for developing reliable biomarkers related to cognitive decline in SIVCIND.